ANALISIS DERAJAT DESENTRALISASI FISKAL KOTA MALANG TAHUN 2004-2008 - Tiyaningsih, Andarini Agus (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2009)
The purpose of my research is to find desentralisasi degree fiscal of Malang city 2004-2008 years old. The analysis tools is desentralisasi degree fiscal include Ratio Pendapatan Asi Daerah (PAD) with Total Penerimaan Daerah (TPD), ratio Bagi Hasil Pajak dan Bukan Pajak (BHPBP) with Total Penerimaan Daerah (TPD) and ratio Sumabngan Daerah (SD) with Total Penerimaan Daerah (TPD). The result of ratio analysis PAD with TPD are 13,05%, the result of ratio analysis BHPBP with TPD are 9,00% and the result of ratio analysis SD withTPD are 8,94%. Such was the case the result of that analysis is Malang was not independent, because the biggest fund of central goverentment, and Pendapatan Asli Daerah (PAD) of Malang is low.